Arctic East Siberia had a lower latitude in the Pleistocene - Willy Woelfli (Anais da Academia Brasileira de Ciências, 2007)
Remains of mammoths in Arctic East Siberia, where there is not sufficient sunlight over the year for the growth of theplants on which these animals feed, indicate that the latitude of this region was lower before the end of the Pleistocenethan now. Reconstructing this geographic pole shift, we introduce a massive object, which moved in an extremelyeccentric orbit and was hot from tidal work and solar radiation. Evaporation produced a disk-shaped cloud of ionsaround the Sun. This cloud partially shielded the solar radiation, producing the cold and warm periods characterizingthe Pleistocene. The shielding depends on the inclination of Earths orbit, which has a period of 100.000 years.The cloud builds up to a point where inelastic particle collisions induce its collapse The resulting near-periodic timedependence resembles that of Dansgaard-Oeschger events. The Pleistocene ended when the massive object had a closeencounter with the Earth, which suffered a one per mil extensional deformation. While the deformation relaxed to anequilibrium shape in one to several years, the globe turned relative to the rotation axis: The North Pole moved fromGreenland to the Arctic Sea. The massive object split into fragments, which evaporated